Seismic analysis of thin shell catenary vaults - Surat, Daniel (My University, 2017)
This report investigates the seismic response of catenary vaults. Through a series of tests, the inherent seismic resilience of catenary vaults was assessed and a number of reinforcement strategies were investigated to improve this. An analytical model, based on the virtual work method, was developed by Ochsendorf (2002) for the assessment of circular voussoir arches. This model was adapted for catenary vaults. This model is used to calculate the minimum lateral acceleration required to cause the collapse of a catenary vault (λmin) for any catenary profile. The model indicates that there is a linear relationship between cross sectional depth of the arch and λmin until the depth to ratio passes approximately 0.3, where the change in λmin becomes exponential. Using the model, it is also predicted that λmin decreases exponentially with an increase in the height to width ratio up to a value of approximately 1.6. After this point λmin linearly decreases with increased height to width ratios and approaches zero. The first series of tests involved subjecting unreinforced catenary vaults to seismic loading. In these tests the frequency of vibration was varied and the stroke was kept constant. From the results of the tests, it was found that there was no frequency at which the vaults underwent excessive vibration due to resonance. It was observed that during seismic loading, hinges form at locations where pre-existing cracks occur despite the higher computed λmin values for these positions. The tests also indicate that the vaults’ behaviour changes drastically with each hinge that forms. In the next series of tests the frequency was set and the stroke was increased. The vaults were subjected to seismic loading at 2 Hz and 6 Hz, representative of low and high frequencies respectively. The tests indicated that the collapse acceleration of arches subjected to vibration at 2 Hz was lower than that of the vaults subjected to vibrations at 6 Hz. Despite this, the stroke, representing ground movement, required to cause collapse at 2 Hz was substantially higher than that of the 6 Hz tests. This indicates that the duration of load cycles has an effect on the collapse acceleration. In comparing the computed collapse acceleration, λmin, with the actual collapse accelerations, it was found that the computed values are highly conservative. Yet this is expected as the model is based on an infinite duration of lateral loading. It was found that the analytical model was more accurate for low frequency tests as compared to high frequency tests in terms of the predicted hinge locations. Finally, three reinforcement strategies were investigated using basalt fibre geogrid. This was found to be an economical and viable reinforcement material. The first strategy consisted of laying the geogrid over the arch and securing it at the arch base. The second was the same as the first with the addition of anchors which held the geogrid down. The final strategy involved prestressing the arch using the geogrid. The latter 2 methods were found to be the most effective, with observed collapse accelerations being over 60% higher than that of the same unreinforced arch. The anchorage solution was found to be the most viable due to the substantially higher technical input required for the prestressing solution.
Research report submitted to the Faculty of Engineering and the Built Environment, University of Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Engineering Johannesburg 2017
Keywords: Seismology; Structural analysis (Engineering); Catenary; Vaults (Architecture)